2019
DOI: 10.1002/chem.201806345
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Photocatalyzed Borylation of Organic Halides under Batch and Continuous‐Flow Conditions

Abstract: The copper-photocatalyzed borylation of aryl, heteroaryl, vinyl and alkyl halides( Ia nd Br) was reported. The reaction proceededu sing an ew heteroleptic Cu complex under irradiation with blue LEDs, givingt he corresponding boronic-acid esters in good to excellent yields. The reactionw as extended to continuous-flowc onditions to allow an easy scale-up. The mechanism of the reaction was studied and am echanism based on ar eductive quenching (Cu I /Cu I */Cu 0 )w as suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 61 publications
0
32
0
1
Order By: Relevance
“…Indeed, electrochemical synthesis, by replacing hazardous chemical redox reagents by electrons, avoids the generation of wastes and if electricity is produced from renewable sources, it can be considered as a green process [14] . As part of our program to develop straightforward access to boron‐containing molecules, [15] we sought to use organic electrochemistry to generate boryl radicals that would be used as an unprecedented reaction manifold in the hydroboration of alkynes. Worth of note, during the preparation of this manuscript, Qing and co‐workers reported the electrochemical hydroboration of styrene using HBpin as the boron source and DIPEA as auxiliary [16] .…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, electrochemical synthesis, by replacing hazardous chemical redox reagents by electrons, avoids the generation of wastes and if electricity is produced from renewable sources, it can be considered as a green process [14] . As part of our program to develop straightforward access to boron‐containing molecules, [15] we sought to use organic electrochemistry to generate boryl radicals that would be used as an unprecedented reaction manifold in the hydroboration of alkynes. Worth of note, during the preparation of this manuscript, Qing and co‐workers reported the electrochemical hydroboration of styrene using HBpin as the boron source and DIPEA as auxiliary [16] .…”
Section: Methodsmentioning
confidence: 99%
“…Aryl boronic acid and esters are important building blocks for the formation of aryl carbon–carbon or carbon-heteroatom bonds. 19 Recently, a number of strategies for photo-induced borylation of aryl halides via direct ultraviolet light irradiation, 20 in the presence of a metal-based photocatalyst 8i , 21 or in situ generated electron donor 21 have been developed. At the outset, visible-light-induced borylation of 1-iodo-3,5-dimethylbenzene with bis(pinacolato)-diboron (B 2 Pin 2 ) was chosen as a model reaction with the most commonly used Hunig base (DIPEA) as a reductive quencher.…”
Section: Resultsmentioning
confidence: 99%
“…In early 2019, our research group reported the copperphotocatalyzed borylation of organic halides using [Cu(I)(DMEGqu)(DPEPhos)]PF 6 as the photocatalyst (Scheme 26) [41]. The photocatalytic Miyaura borylation reaction was carried out using aryl iodides bearing either electrondonating or electron-withdrawing groups in good to excellent yields.…”
Section: Reduction Reactionsmentioning
confidence: 99%